Biosafety Analysis of Metabolites of Streptomyces tauricus Strain 19/97 M, Promising for the Production of Biological Products - Irina I. Gaidasheva; Tatiana L. Shashkova; Irina A. Orlovskaya; Tatyana I. Gromovykh (Bioengineering, 2022)
A biosafety study was carried out concerning the metabolites of Streptomyces tauricus strain 19/97 M. This strain is a promising producer of biological preparations and shows antagonistic properties against Fusarium fungi, which cause Fusarium wilt disease. The strain has a pronounced biological activity against conifers, cereals and legumes. The treatment of planting material reduces infections, increases germination and furthers plant productivity. Using metabolites, we understood the culture liquid separated by filtration after the cultivation of the strain. Animals of different taxonomic affiliations were used as test objects: (CBA × C57BI/6) F1 hybrid mice (Mus musculus) (warm-blooded organisms), Daphnia magna Straus (planktonic crustaceans) and the unicellular alga Chlorella vulgaris Beijer. In the study, we were guided by the test standards for acute oral toxicity and irritation to the skin, mucous membranes of the eyes and inhalation toxicity. The research results showed that the metabolites of the strain are not acutely toxic to organisms of different taxonomic levels. The metabolites of the strain do not have an irritating effect on the skin and mucous membranes of warm-blooded animals. Based on the studies carried out, metabolites can be used for creating a fungicidal biological preparation.